Association between upper-limb isometric strength and handcycling performance in elite athletes - Muchaxo, R. E. A.; de Groot, S.; Kouwijzer, I.; van der Woude, L. H. V.; Nooijen, C. F. J.; Janssen, T. W. J. (Sports Biomechanics, 2022)
This study investigated the association among isometric upper-limb strength of handcyclists and sport-specific performance outcomes. At two international events, 62 athletes were tested on upper-limb strength, measured with an isometric-strength setup and with Manual Muscle Test (MMT). Horizontal force (Fz), effectiveness, rate of development, variability, and asymmetries were calculated for upper-limb pull and push. Performance measures were mean (POmean) and peak (POpeak) 20-s sprint power output and average time-trial velocity (TTvelocity). Regression models were conducted to investigate which pull and push strength variables associated strongest with performance measures. Additional regression analyses were conducted with an MMT sum score as predictor. Push and pull Fz showed the strongest associations with all outcomes. Combined push and pull Fz explained (p < .001) 80-81% of variance of POmean and POpeak. For TTvelocity, only push Fz was included in the model explaining 29% of the variance (p < .001). MMT models revealed weaker associations with sprint PO (R2 = .38-.40, p < .001) and TTvelocity (R2 = .18, p = 0.001). The findings confirmed the relevance of upper-limb strength on handcycling performance and the significance of ratio-scaled strength measures. Isometric strength outcomes are adequate sport-specific indicators of impairment in handcycling classification, but future research should corroborate this notion and its potential to discriminate between sports classes.